Increased production of proinflammatory cytokines in adipose tissue of patients with end-stage renal disease - Roubicek, Tomas; Bartlova, Marketa; Krajickova, Jana; Haluzikova, Denisa; Mraz, Milos; Lacinova, Zdena; Kudla, Michal; Teplan, Vladimir; Haluzik, Martin (Nutrition (Burbank, Los Angeles County, Calif.), 2009)
OBJECTIVE: The number of patients with end-stage renal disease (ESRD) is rising and these patients are at higher risk of cardiovascular disease. We studied the role of hormonal production of adipose tissue in the development of chronic inflammation in patients with ESRD before kidney transplantation. METHODS: Fifteen women with ESRD and 17 healthy women (control) underwent single blood drawing and visceral and subcutaneous adipose tissue sampling during surgery (kidney transplantation in the ESRD group or cholecystectomy in the control group). Serum concentrations of C-reactive protein, interleukin-6, tumor necrosis factor-alpha, leptin, adiponectin, resistin, monocyte chemoattractant protein-1 were measured. Messenger RNA expression of the same hormones, adiponectin receptors 1 and 2 and immunocompetent cell marker CD68 in subcutaneous and visceral samples were measured using real-time polymerase chain reaction. Adipose tissue was examined immunohistochemically for CD68-positive cells. RESULTS: Serum concentrations of C-reactive protein, adiponectin, resistin, interleukin-6, tumor necrosis factor-alpha, and monocyte chemoattractant protein-1 were significantly higher in the ESRD versus control group. Subcutaneous and visceral mRNA expressions of tumor necrosis factor-alpha and CD68 were significantly increased in the ESRD versus control group. Adiponectin receptor-1 and monocyte chemoattractant protein-1 mRNA expressions were significantly higher in visceral but not in subcutaneous adipose tissue of the ESRD group. Messenger RNA expressions of resistin, leptin, adiponectin, interleukin-6, and adiponectin receptor-2 in both fat depots did not significantly differ between groups. Increased infiltration of subcutaneous and visceral adipose tissue with CD68-positive immunocompetent cells was found in the ESRD group by histologic examination. CONCLUSION: Subcutaneous and visceral adipose tissues in ESRD express higher amounts of proinflammatory cytokines and may play a role in the development of systemic inflammation.
Keywords: Resistin; receptory adiponektinu; Female; Cytokines; chronické selhání ledvin; adiponektin; C-Reactive Protein; Tumor Necrosis Factor-alpha; ženské pohlaví; CD antigeny; cytokiny; Adiponectin; lidé; podkožní tuk; Inflammation Mediators; Intra-Abdominal Fat; Subcutaneous Fat; messenger RNA; Interleukin-6; Kidney Failure, Chronic; antigeny diferenciační myelomonocytární; RNA, Messenger; Antigens, CD; Receptors, Adiponectin; chemokin CCL2; TNF-alfa; Chemokine CCL2; interleukin-6; nitrobřišní tuk; resistin; mediátory zánětu; C-reaktivní protein; lidé středního věku; Middle Aged; Antigens, Differentiation, Myelomonocytic; Humans